(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The Chersonissos fountain with step was found at the end of the XIX century in an area overlooking the sea, in the lower part of the modern city, a few miles east of Iraklion, together with other ruins of the Roman period. The polychrome tesserae decoration represents a water illustration. The scenes depict people either fighting or surrounded by animals. The human characters represented in the mosaics appear smaller than the animals, which, together with their nakedness and the Negroid traits of their bodies and faces, suggest that they are Pigmies. Although the iconography gleans from a rather widespread repertory, both because of the fishy sea with scenes of fishermen catching fish and because of the Nilotic landscape, these decorations are unique on the technical-stylistic point of view.